2020
DOI: 10.3390/atmos11020204
|View full text |Cite
|
Sign up to set email alerts
|

Regulated and Non-Regulated Emissions from Euro 6 Diesel, Gasoline and CNG Vehicles under Real-World Driving Conditions

Abstract: The transport sector is one of the main sources air pollutants. Different exhaust after-treatment systems have been implemented over the years to control the emissions of criteria pollutants. However, while reducing the emissions of the target compounds these systems can lead to the emissions of other pollutants and/or greenhouse gases such as NH 3 or N 2 O. Following the implementation of the Real Driving Emissions (RDE) test procedure in the EU, vehicles have been equipped with more complex after-treatment c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
36
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 70 publications
(48 citation statements)
references
References 52 publications
11
36
1
Order By: Relevance
“…In this study, we measured the emissions of regulated and non-regulated pollutants of a diesel fueled vehicle both in the laboratory and on the road. For all regulated testing conditions, all currently regulated pollutants were below the applicable limits, in agreement with other studies of Euro 6d-temp diesel vehicles [45,46]. Particularly for NO x , which was the main attention topic for diesel vehicles until very recently, the emissions were below the applicable (and future) limits on the road even when DPF regeneration events occurred, and much lower compared to the pre-RDE Euro 6 diesel vehicles that were typically emitting on the road >4 times the limit [23,29,[54][55][56][57].…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…In this study, we measured the emissions of regulated and non-regulated pollutants of a diesel fueled vehicle both in the laboratory and on the road. For all regulated testing conditions, all currently regulated pollutants were below the applicable limits, in agreement with other studies of Euro 6d-temp diesel vehicles [45,46]. Particularly for NO x , which was the main attention topic for diesel vehicles until very recently, the emissions were below the applicable (and future) limits on the road even when DPF regeneration events occurred, and much lower compared to the pre-RDE Euro 6 diesel vehicles that were typically emitting on the road >4 times the limit [23,29,[54][55][56][57].…”
Section: Discussionsupporting
confidence: 90%
“…Only dynamic driving brought the NO x levels (200 mg/km) slightly higher than the limit (168 mg/km, using the applicable 2.1 conformity factor). Others have also reported that dynamic driving significantly increases the emissions [36,46]. The NO/NO x ratio was on average 78% in the laboratory tests and 65% in the on-road tests.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…It was found that vehicles fueled with diesel emitted significantly more N 2 O than the vehicles fueled with gasoline, E85 and the hybrid vehicles (p value of 4•10 −10 , 0.0008 and 0.0002, respectively). These findings are consistent with the results obtained over on-road tests where N 2 O emissions from two LDV gasoline were found non-detectable while two LDV diesel where emitting up to 27 mg/km [54]. High N 2 O emissions from diesel fueled LDV (ca.…”
Section: Effect Of the Fuel And Engine Technology On Ch 4 And N 2 O Esupporting
confidence: 91%